2011
DOI: 10.1002/ps.2163
|View full text |Cite
|
Sign up to set email alerts
|

Protective and curative efficacy of prothioconazole against isolates of Mycosphaerella graminicola differing in their in vitro sensitivity to DMI fungicides

Abstract: A protective application of prothioconazole in wheat crops could be the best strategy to keep a high efficacy against Septoria leaf blotch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Previous research has shown that reduced rates of the DMI fungicide flutriafol exhibited reduced efficacy to control CLS compared with the full recommended rate (24). In contrast, a recent experiment on the effect of prothioconazole rate on disease caused by M. graminicola showed that application rate had no differential effect on disease-causing ability of three high EC50 value isolates (37). The finding that the high EC50 value isolate caused significantly more disease than the medium or low EC50 value isolates at the field rate suggests that the EC50 value of 1.0 |jg ml"' is a valid threshold above which isolates may be considered DMI resistant.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous research has shown that reduced rates of the DMI fungicide flutriafol exhibited reduced efficacy to control CLS compared with the full recommended rate (24). In contrast, a recent experiment on the effect of prothioconazole rate on disease caused by M. graminicola showed that application rate had no differential effect on disease-causing ability of three high EC50 value isolates (37). The finding that the high EC50 value isolate caused significantly more disease than the medium or low EC50 value isolates at the field rate suggests that the EC50 value of 1.0 |jg ml"' is a valid threshold above which isolates may be considered DMI resistant.…”
Section: Discussionmentioning
confidence: 81%
“…DMIs have gained popularity due to protective and curative properties and low levels of phytotoxicity (10,37). DMI-resistant isolates initially were thought to cause less disease than DMIsensitive isolates, suggesting that DMI resistance would not become widespread in field populations (11,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, application of fungicides, mainly the sterol 14α-demethylase inhibitors (DMIs), remained as the main method for controlling this disease (Gouache et al, 2009;Sanssené et al, 2011;Somai-Jemmali et al, 2014). However, a high proportion of DMI-moderate resistant genotypes (≥94%) was recently recorded Selim, 2009;.…”
Section: Introductionmentioning
confidence: 99%
“…The fungicide prothioconazole was introduced to the European market in 2002 and is widely used to control M. graminicola and other pathogens in cereals (Dutzmann, Suty-Heinze, 2004;Sanssene et al, 2011). Prothioconazole has been sold in commercial mixtures with tebuconazole (Prosaro) and spiroxamine (Input) in Lithuania since 2006.…”
Section: Discussionmentioning
confidence: 99%